The effect of credibility assessment techniques on consistency and subsequent memory for the truth - Dianiska, Rachel E.; Meissner, Christian A. (Frontiers in Psychology, 2023)
Repeated interviews are common during an investigation, and perceived consistency between multiple statements is associated with an interviewee’s credibility. Furthermore, research has shown that the act of lying can affect a person’s memory for what truthfully occurred. The current study assessed the influence of lying on memory during initial and repeated interviews, as well as how an interviewer’s approach might affect between-statement consistency for true and false statements. Participants performed a scavenger hunt at two sets of buildings on a university campus and then were either dismissed or interviewed (with a Reverse Order instruction or a Structured Interview) about their activities. Participants chose one set to tell the truth about and then created a lie about activities in another area of campus that had not been visited. One week later, all participants provided a second free recall statement about their activities during the scavenger hunt, and then a final truthful description of both areas that were visited during the scavenger hunt. Truthfully rehearsed experiences were associated with more accurate recall of information learned during the scavenger hunt as well as more consistent and more detailed statements. The Structured Interview led to initially more detailed statements, but more inconsistencies in the form of omissions.